PERUBAHAN PEMENTASAN BEDHAYA KETAWANG PASCA KEMERDEKAAN REPUBLIK INDONESIA - Hadawiyah Endah Utami (Institut Seni Indonesia Surakarta, 2012)
The change of the world happened along age. Human culture stated many important events in their lifetime. It was same as dance performance ofBedhaya Ketawang that has been major performance in event of king’s tingalan jumenengan. It was a phenomena cultur either political or art culture both of which nice to review. Its performance sometimes ago has evidenced many changes. The most issue was kasunanan palace lost its hegemony of power caused by independence revolution in 1945. Bedhaya Ketawang as a performance of political art related to the power has same effect. Bedhaya Ketawang was not symbol of political statement anymore, however, it was inclined be usual culture like other dance presented for audiences; that was a dance performance called pseudo-ritual. Key words : the change, Bedhaya, ritual Pengantar